2018
DOI: 10.1515/cpp-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Eveningness and its possibility of predicting burnout symptoms among physicians and nurses – preliminary results

Abstract: Introduction. A sense of burnout may seriously impair one’s functioning and well-being. It may also hamper the quality of care over a patient. The present study therefore assesses sleep quality and chronotype as predictors of a sense of burnout in physicians and nurses of a district hospital. Material and methods. The study group comprised 16 physicians and 31 nurses of a district hospital in Central Poland. The participants completed the Link Burnout Questionnaire (LBQ), Chronotype Questionnaire, and Pittsbur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Although the link between DI and Psychophysical Exhaustion scores identified in the present study reflects those identified in the previous research on physicians and nurses, the link between DI and Disillusionment does not (Mokros et al 2018). This disjunction may have influenced the specificity of the results and the observed differences between the studied samples; clearly, further verification is required.…”
Section: Hypothesissupporting
confidence: 48%
See 2 more Smart Citations
“…Although the link between DI and Psychophysical Exhaustion scores identified in the present study reflects those identified in the previous research on physicians and nurses, the link between DI and Disillusionment does not (Mokros et al 2018). This disjunction may have influenced the specificity of the results and the observed differences between the studied samples; clearly, further verification is required.…”
Section: Hypothesissupporting
confidence: 48%
“…It has also been associated with significant burnout and poor wellbeing in young adults (Gulec et al 2013;Merikanto et al 2016). It has been found that late chronotype can predict high psychophysical exhaustion, high relationship deterioration and an increased sense of professional ineffectiveness among physicians and nurses (Mokros et al 2018). Interestingly, this evening type may not only hamper mental status, but also increase the incidence of comorbid somatic diseases (Sahbaz et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that MD students tend to be more evening types than their peers, and since their workload is greater, this can also impact their wellbeing. Morningness-eveningness orientation should be considered as a significant risk factor for burnout, as observed in evening types [ 45 ]. Furthermore, evening-oriented individuals tend to have more depressive symptoms, as well as cognitive and behavioral problems, experiencing hyperactivity, attention deficit and tending towards impulsivity [ 21 , 46 ].…”
Section: Discussionmentioning
confidence: 99%